Formation of biofilm on implant surfaces and its impact on implant homeostasis - LIU Yuhan, MENG Weiyan (Kouqiang yixue)
Peri-implant mucositis and peri-implantitis are among the primary risk factors for the failure of dental implants, with plaque biofilm being the initiating factor for these peri-implant diseases. This paper reviews the formation process of plaque biofilm on implant surfaces, the influencing factors of its formation, and its impact on implant homeostasis. It provides insights for the removal of plaque biofilm and the improvement of implant success rates.